Implementation Of The Principle Of Publicity In The Complete Systematic Land Registration Program From The Perspective Of Legal Certainty In Semarang City - Yusuf, Fayeza Nafesyah; Riyanto, Taufan Fajar; Arifulloh, Achmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
The aim of this research isto analyze the implementation of the principle of publicity in the PTSL program has not been able to guarantee legal certainty at the Semarang City Land Office, and the factors that hinder it. The research method used in this study is: the type of research used in this study is empirical legal research, the approach method used is the structural approach and Economic Analysis of Law. The data used is primary data with qualitative descriptive data analysis. The results of the study show that the implementation of the principle of publicity in the PTSL program has not been able to guarantee legal certainty at the Semarang City Land Office, because it uses a negative publication system with positive elements as regulated in Article 24 of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 6 of 2018 concerning PTSL. This means that the State does not guarantee the accuracy of the data presented. For landowners, even though they have been listed as landowners in the certificate, they can still face the possibility of being sued in court by parties who have an interest in the land, meaning that the land title certificate can still be canceled. In 2022-2023, there were 111 certificate lawsuits that were decided by the Semarang District Court Judge, and 16 certificates were canceled by the Semarang State Administrative Court. The inhibiting factors can be seen from 3 (three) angles, namely: First, the legal substance (substance of the law), there are weaknesses in Article 24 of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 6 of 2018 concerning PTSL, related to the use of a negative publication system with positive elements, this causes legal uncertainty, because there is still a possibility of court lawsuits from parties who feel they have an interest in the land; Second, the legal structure (structure of law), namely the limited implementing resources, especially survey officers and administrative staff; and Third, legal culture (legal culture), namely the level of community participation is still low, and the occurrence of internal disputes between families or heirs.